LANGUAGE LEARNING IS TREATMENT TO HUMAN HEALTH - Xaliqova, Ra’no (Журнал иностранных языков и лингвистики, 2021)
Annotation: Today 60-70 percent of world population is bilingual. Each person has his own goal for learning language. However, there is one more precious property that can be obtain by learning language. It is – health. After many researches, scientists declared the significant benefits of learning language to human health. Key words: Health, highly developed substance, bilingualism, brain, diseases, Alzheimer, dementia, neuroscientist, stroke.